Sulforaphane prevents human platelet aggregation through inhibiting the phosphatidylinositol 3-kinase/Akt pathway - Chuang, Wen-Ying; Kung, Po-Hsiung; Kuo, Chih-Yun; Wu, Chin-Chung (Thrombosis and Haemostasis, 2013)
Sulforaphane, a dietary isothiocyanate found in cruciferous vegetables, has been shown to exert beneficial effects in animal models of cardiovascular diseases. However, its effect on platelet aggregation, which is a critical factor in arterial thrombosis, is still unclear. In the present study, we show that sulforaphane inhibited human platelet aggregation caused by different receptor agonists, including collagen, U46619 (a thromboxane A2 mimic), protease-activated receptor 1 agonist peptide (PAR1-AP), and an ADP P2Y12 receptor agonist. Moreover, sulforaphane significantly reduced thrombus formation on a collagen-coated surface under whole blood flow conditions. In exploring the underlying mechanism, we found that sulforaphane specifically prevented phosphatidylinositol 3-kinase (PI3K)/Akt signalling, without markedly affecting other signlaling pathways involved in platelet aggregation, such as protein kinase C activation, calcium mobilisation, and protein tyrosine phosphorylation. Although sulforaphane did not directly inhibit the catalytic activity of PI3K, it caused ubiquitination of the regulatory p85 subunit of PI3K, and prevented PI3K translocation to membranes. In addition, sulforaphane caused ubiquitination and degradation of phosphoinositide-dependent kinase 1 (PDK1), which is required for Akt activation. Therefore, sulforaphane is able to inhibit the PI3K/Akt pathway at two distinct sites. In conclusion, we have demonstrated that sulforaphane prevented platelet aggregation and reduced thrombus formation in flow conditions; our data also support that the inhibition of the PI3K/Akt pathway by sulforaphane contributes it antiplatelet effects.
Keywords: Platelet aggregation; sulforaphane; phosphatidylinositol 3-kinase; ubiquitination